Muslim Community in the Atmosphere of Populism in Norway - Mahadika, Gilang (Global: Jurnal Politik Internasional, 2021)
In the European nations, there has been a lot of discussions and arguments regarding the community who have a ‘migration background’. Migrants nowadays are more capable of competing against local residents in terms of looking for better employment and participating in the political activities in European countries. Consequently, it creates fear within ‘mainstream’ society since it is presumably able to threaten their way of life. This interesting moment can benefit the populist political parties for gaining voices from the majority population. But, in the aftermath of 22/7 terror attacks in Norway, it also created tension between locals and those who are considered having a ‘migration background’. The people who have migration background, especially Muslim community, already has long history of migration to Norway. Therefore, the research question is how the Muslim community adapt to the situation of populism in Norway. By using historical literatures and research articles regarding the aftermath of 22/7 terror attack, it shows that the intersectional approach is useful to see the intermingled aspects of class, identity, religion, nationality, gender, and ethnicity of marginalised communities. These migrants now are facing multiple discriminations. Protests in the public sphere as a way of adapting to the atmosphere of populism are considered as their struggles for citizenship since the government seems to fail at managing multicultural society, especially advocating the minority groups. This kind of situation is common in the era of populism emerging in many countries targeting minority groups as political manoeuvre in order to gain voices among the ‘common’ society.